1998
DOI: 10.1007/s002619900415
|View full text |Cite
|
Sign up to set email alerts
|

Choledochal cysts: evaluation with MR cholangiography

Abstract: MR cholangiography can be used to confirm the diagnosis of choledochal cysts and define the extent of involvement preoperatively. The pancreatobiliary junction, however, is difficult to visualize. Non-biliary cysts such as a hydatid cyst can mimic a choledochal cyst on the MR cholangiogram and should be correlated with the MR cross-sectional images to avoid misinterpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…MR cholangiopancreatography is a noninvasive procedure and provides the best available projection image for revealing the extent of choledochal cyst in children and adults [8][9][10][11][12][13][14][15]. Researchers have reported that anomalous pancreaticobiliary ductal union can be depicted in adult patients on MR cholangiopancreatography with a half-Fourier single-shot fast spin-echo or turbo spin-echo sequence [12,13,15], but that this finding was not shown in children when a turbo spin-echo or an inversion recovery turbo spin-echo sequence with maximum intensity projection was used [9,10].…”
mentioning
confidence: 99%
“…MR cholangiopancreatography is a noninvasive procedure and provides the best available projection image for revealing the extent of choledochal cyst in children and adults [8][9][10][11][12][13][14][15]. Researchers have reported that anomalous pancreaticobiliary ductal union can be depicted in adult patients on MR cholangiopancreatography with a half-Fourier single-shot fast spin-echo or turbo spin-echo sequence [12,13,15], but that this finding was not shown in children when a turbo spin-echo or an inversion recovery turbo spin-echo sequence with maximum intensity projection was used [9,10].…”
mentioning
confidence: 99%
“…August 28, 2013|Volume 5|Issue 8| WJR|www.wjgnet.com [47] 4 4 Sugiyama et al [22] 1 2 Irie et al [56] 0 2 Matos et al [57] 2 2 Govil et al [58] 3 3 Frampas et al [54] 3 3 Kim et al [60] 8 8 Park et al [55] 8 8 Suzuki et al [61] 15 years, employing different designs, techniques, and gold standards as imaging and detection protocols have evolved. Due to those improvements, contemporary detection rates are possibly higher than what our cumulative data indicates.…”
mentioning
confidence: 99%
“…Pancreatic pseudocyst can be confirmed or excluded on the basis of clinical history and presentation. Choledochal cyst and gallbladder duplication can be correctly diagnosed with MR imaging if the lesion is found to communicate with the biliary duct system [10,11].…”
Section: Discussionmentioning
confidence: 98%